2019
DOI: 10.1111/jce.14307
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the left atrial ridge (coumadin ridge) and possible clinical implications for cardiovascular imaging and invasive procedures

Abstract: Background: The left atrial ridge is a structure located in the left atrium between the left-sided pulmonary veins ostia and the orifice of the left atrial appendage. Since it was commonly misdiagnosed as a thrombus, the ridge is also known as the "coumadin" or "warfarin" ridge. The left atrial ridge is a potential source of arrhythmias and can be an obstacle in ablation procedures. This study aimed to provide information about the occurrence and spatial morphometric characteristics of the left atrial ridge. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…RF ablation is sometimes difficult to achieve transmural lesion due to the thickness of atrial wall, for example, in the left lateral ridge which is both part of MI and insertion of epicardial connection. 17 The left circumflex artery, CS" and great cardiac vein locate in the middle to lower part of epicardial MI, causing a heat sink effect that further hinders the delivery of RF energy, but intensive RF application should be avoided in these cases to minimize the risk of injury to the vessels. 3 Moreover, epicardial connections are common and usually have multiple insertions to the left atrium.…”
Section: Ei-vom Overcomes MI Anatomic Obstacles In Rf Ablationmentioning
confidence: 99%
“…RF ablation is sometimes difficult to achieve transmural lesion due to the thickness of atrial wall, for example, in the left lateral ridge which is both part of MI and insertion of epicardial connection. 17 The left circumflex artery, CS" and great cardiac vein locate in the middle to lower part of epicardial MI, causing a heat sink effect that further hinders the delivery of RF energy, but intensive RF application should be avoided in these cases to minimize the risk of injury to the vessels. 3 Moreover, epicardial connections are common and usually have multiple insertions to the left atrium.…”
Section: Ei-vom Overcomes MI Anatomic Obstacles In Rf Ablationmentioning
confidence: 99%
“…The occurrence of a prominent fold is likely when the LSPV and LAA are in a close anatomical relationship. In such cases, the ridge might be even thicker, which could result in a worse AF-free survival after ablation ( 22 ). Another previous study found that bilateral ridge ablation improves arrhythmia-free survival compared to PVI-only in case of paroxysmal AF ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The LAR is an invagination located between the left PVs and the LAA. A recent cadaveric study by Piątek‐Koziej et al 1 revealed that the appearance of LAR varies, with an average width of 7.9 ± 3.2 mm and whole wall thickness of 4.3 ± 1.8 mm at the LSPV ostium. However, in our study, we measured a smaller preprocedural width of 5.2 ± 1.6/5.7 ± 2.2 mm and a larger thickness of 11.0 ± 3.8/13.1 ± 4.1 mm at 45°/90° planes.…”
Section: Discussionmentioning
confidence: 99%
“…The left atrial ridge (LAR)—also known as the coumadin ridge—is a protruding structure located between the left atrial appendage (LAA) and left pulmonary veins (PV). The LAR is also a potential source of arrhythmias and a site of ablation, where it is close to autonomic nervous fibers, Bachmann's bundle, and Marshall′s ligament 1 . LAR had long been a site for atrial fibrillation (AF) ablation 2 and one of the differential diagnosis points of high‐echo band on echocardiography 3 …”
Section: Introductionmentioning
confidence: 99%